5-LO inhibition ameliorates palmitic acid-induced ER stress, oxidative stress and insulin resistance via AMPK activation in murine myotubes - Hyun Jeong Kwak (Nature Portfolio, 2017)
Abstract Leukotriene B4 (LTB4) production via the 5-lipoxygenase (5-LO) pathway contributes to the development of insulin resistance in adipose and hepatic tissues, but the role of LTB4 in skeletal muscle is relatively unknown. Here, the authors investigated the role of LTB4 in C2C12 myotubes in palmitic acid (PA)-induced ER stress, inflammation and insulin resistance. PA (750 μM) evoked lipotoxicity (ER stress, oxidative stress, inflammation and insulin resistance) in association with LTB4 production. 5-LO inhibition reduced all the lipotoxic effects induced by PA. On the other hand, PA did not induce cysteinyl leukotrienes (CysLTs), which themselves had no effect on ER stress and inflammation. The beneficial effects of 5-LO suppression from PA-induced lipotoxicity were related with AMPK activation. In ob/ob mice, once daily oral administration of zileuton (50, 100 mg/kg) for 5 weeks improved insulin resistance, increased AMPK phosphorylation, and reduced LTB4 and ER stress marker expression in skeletal muscle. These results show that 5-LO inhibition by either zileuton or 5-LO siRNA protects C2C12 myotubes from PA-induced lipotoxicity, at least partly via AMPK activation, and suggest that the in vivo insulin-sensitizing effects of zileuton are in part attributable to its direct action on skeletal muscle via LTB4 downregulation followed by AMPK activation.